Maternal risk and neonatal problems (Colombia Medica, 1993)
In the level three hospital of Cali, the Hospital Universitario del Valle, data were collected in a blind study to examine the relationship between the presence of risk factors in the mothers and the appearance of neonatal problems. From August 1, 1990, through April 1, 1991, 500 mothers and children who died were studied. They were collected in an aleatory way, and every fifth mother admitted for delivery went into the study with her newborn independently of any other consideration. Of the 500 hundred mothers, 112 did not have any risk factor(22.5%); 128 (25.7%) had one risk factor; 129 (25.9%) had two risk factors, and 129 (25.9%) had three or more risk factors. According to the bibliography about the subject and the associated neonatal problems, 24 maternal risk factors were chosen. Premature delivery was the mother's factor most important associated with neonatal problems (73%), with an IRR for LBW of 148, for neonatal infections of 41.7, for RDS of 27, for neonatal infections of 21.6, for metabolic problems of 11.6 and the mortality rate risk was increased 14 times in this group. The last trimester pregnancy hemorrhage had an IRR of 15.2 for the appearance of an abnormal neurological examination, 13.7 for prematurity, 10 for perinatal asphyxia, and 7.3 for LBW. The most frequent neonatal problems were LBW (19%), perinatal asphyxia (14.8%), prematurity (13.5%), abnormal neurological physical examination ( 10.8%), and intrauterine growth retardation (IUGR) (7.8%). Prematurity was 63.3% of the LBW babies, and IUGR was the cause of 36.6% of the LBW. The main maternal risk factors associated with prematurity were Jast trimester pregnanéy hemorrhage (RRI: 13.7), chorioamnionitis (RRI: 6.5), and urinary tract infection (RRI: 6). These factors need further investigation and research for proposing intervention models. For IUGR, a positive VDRL (IRR: 7.3), a maternal prepregnancy weight (PPW) less than 45 kilograms (IRR: 6), and the fact of the mother being alone (without the father) at the end of the pregnancy (RRI: 2.3) were associated with it. The perinatal mortality of the ample was 54 per thousand. Of it, 81.5% was fetal, and 18.5% was neonatal.